Preliminary Experience With a Novel Metallic Segmented Transcordal Stent Modified With Three-Dimensional Printing for Inoperable Malignant Laryngotracheal Stenosis - Shan, Qungang; Huang, Wei; Wang, Ziyin; Xue, Qingsheng; Shi, Zhihong; Zhou, Jianping; Wu, Zhiyuan; Ding, Xiaoyi; Mao, Aiwu; Shang, Mingyi; Wang, Zhongmin (Frontiers in Oncology, 2021)
Background This study aims to assess the feasibility of a novel metallic segmented transcordal stent modified with three-dimensional (3D) printing for treating inoperable malignant laryngotracheal stenosis and the tolerability of the stent. Methods This was a retrospective study. The stents were individually customized with the aid of 3D printing model based on the anatomic features of each patient’s airway. The stent was composed of two separate segments that corresponded to the larynx and the upper trachea. The stents were barrel-shaped at the proximal end to prevent migration. The proximal end of the stent was located slightly above the vocal cord. The technical and clinical success of stenting procedure, patient tolerability, and stent-related complications of patients were evaluated. Results Ten patients with dyspnea caused by malignant laryngotracheal stenosis underwent implantation of such stents. Technical and clinical success of the stenting procedure were achieved in all patients. For all patients, basic communication in life could be maintained by speaking softly. During follow-up, one patient showed intolerance to the stent, and the stent was retrieved 2 weeks after stenting. Stent migration was found in one patient, and the position of the stent was readjusted. Granulation tissue proliferation was found in two patients and was treated with cryotherapy by bronchoscopy. There were no deaths associated with stenting. Conclusions The individually customized metallic segmented transcordal stent is feasible and tolerable for patients with inoperable malignant laryngotracheal stenosis. The implantation of this stent may serve as a novel alternative treatment for patients who are not suitable for surgery or tracheotomy.